Anatomy of a murder [videorecording (DVD)] - Ellington, Duke, 1899-1974 (Columbia classics (DVD videodiscs), 2000)
"Emotions flare as a jealous Army lieutenant pleads innocent to murdering the rapist of his seductive, beautiful wife"--Container